Exploring the interplay between evolution and climate change in shaping Potamonautes freshwater crab distributions of South Africa - Grobler, Petrus Cornelius Jacobus (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.